Psychotropic medication utilisation in adult cancer patients in China: A cross-sectional study based on national health insurance database - Lin Bai; Ziyue Xu; Cong Huang; Yunchuan Sui; Xiaodong Guan; Luwen Shi (The Lancet Regional Health. Western Pacific, 2020)
Background: Psychotropic medications are useful to treat psychiatric disorders which are frequently underdiagnosed and undertreated in cancer patients. Evidence on utilisation of psychotropic medications in cancer patients was absent in China. This study aimed to analyse the prevalence and the potential predictors of psychotropic medication use in adult cancer patients in China. Methods: We analysed cross-sectional data from the China Health Insurance Association database in 2015–2017, which contained health care utilisation information for a national representative sample of basic medical insurance beneficiaries. Cancer patients aged above 18 were identified by International Classification of Disease 10th revision code C00–C97. Psychotropic medications were defined following the Anatomical Therapeutic Chemical codes: antipsychotics (N05A), anxiolytics (N05B), hypnotics and sedatives (N05C), and antidepressants (N06A, N06CA). We calculated the prevalence of psychotropic medication use in cancer patients, and applied multivariable logistic regression to identify its potential predictors. Findings: A total of 260,364 adults with cancer were identified in the database, of which 48,111 (18•5%) were prescribed at least one psychotropic medication comprising antipsychotics (3763, 1•4%), anxiolytics (15,902, 6•1%), hypnotics and sedatives (37,040, 14•2%), and antidepressants (2379, 0•9%). Patients with solid tumours had higher prevalence of psychotropic medication use than patients with lymphoid and hematopoietic malignancies (e.g. female genital organs, adjusted odds ratio (OR)=2•25, 95%CI=2•09–2•44). The prevalence of psychotropic medication use in cancer patients in the Eastern region was significantly higher than those of cancer patients in the Western regions (OR=2•33, 95%CI=2•27–2•40). Compared with the Urban Rural Resident Basic Medical Insurance beneficiaries, cancer patients covered by the Urban Employee Basic Medical Insurance were more likely to use psychotropic medications (OR=1•18, 95%CI=1•15–1•20). Midazolam was the most frequently used psychotropic (21,728, 45•2%), and flupentixol–melitracen was the most commonly used antidepressant (1176, 2•4%) among all psychotropic medication users in the sample. Interpretation: The prevalence of psychotropic medication use in Chinese adult cancer patients was inequitable. Further attention will be needed to be paid to the mental health of cancer patients in China. Funding: No funding.